2019
DOI: 10.1007/s12671-019-01107-9
|View full text |Cite
|
Sign up to set email alerts
|

MYmind: a Concurrent Group-Based Mindfulness Intervention for Youth with Autism and Their Parents

Abstract: Objectives The current study evaluated the use of MYmind, a concurrent mindfulness program in which youth with autism and their parents simultaneously receive group specific mindfulness training. Youth with autism can experience emotional and behavioral challenges, which are associated with parental stress. Mindfulness-based programs are emerging as a promising support for these challenges, for both children and parents. While two studies have documented the use of concurrent parentchild programs, neither invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 41 publications
(51 reference statements)
3
44
0
Order By: Relevance
“…For children on the autism spectrum, previous MBP studies not restricted to yoga have shown gains on emotional and behavioral outcomes (Koenig et al, 2012; Ridderinkhof et al, 2018; Rosenblatt et al, 2011; Salem-Guirgis et al, 2019; Singh, Lancioni, Manikam, et al, 2011; Singh, Lancioni, Singh, et al, 2011), executive functions (Chan et al, 2013), memory recall (Chan et al, 2015), sleep and gastrointestinal issues (Narasingharao et al, 2017), autism symptom severity (Sotoodeh et al, 2017), and parasympathetic dominance measured by heart-rate variability (Vidyashree et al, 2019).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For children on the autism spectrum, previous MBP studies not restricted to yoga have shown gains on emotional and behavioral outcomes (Koenig et al, 2012; Ridderinkhof et al, 2018; Rosenblatt et al, 2011; Salem-Guirgis et al, 2019; Singh, Lancioni, Manikam, et al, 2011; Singh, Lancioni, Singh, et al, 2011), executive functions (Chan et al, 2013), memory recall (Chan et al, 2015), sleep and gastrointestinal issues (Narasingharao et al, 2017), autism symptom severity (Sotoodeh et al, 2017), and parasympathetic dominance measured by heart-rate variability (Vidyashree et al, 2019).…”
mentioning
confidence: 99%
“…Several non-randomized studies with parent involvement are reported in the literature. Three studies conducted parallel mindful parenting and mindful awareness for children group programs (MYmind; de Bruin et al, 2015; Ridderinkhof et al, 2018; Salem-Guirgis et al, 2019). Some primarily taught mothers, who then educated their children in the MBP technique (Hwang et al, 2015; Singh, Lancioni, Manikam, et al, 2011).…”
mentioning
confidence: 99%
“…Regarding adolescents and young adults, three studies have also addressed ER difficulties in this population using mindfulness-based programs (Conner & White, 2018;de Bruin, Blom, Smit, van Steensel, & Bögels, 2015;Salem-Guirgis et al, 2019). De Bruin et al (2015), Ridderinkhof, de Bruin, Blom, and Bögels (2018), and Salem-Guirgis et al (2019) examined the feasibility and efficacy of the MYmind Program, a mindfulness-based intervention for adolescents and young adults.…”
Section: Bulletin Of the Menninger Clinicmentioning
confidence: 99%
“…Various measurements were used among the studies and consistent findings were found that adolescents with ASD had improved social responsiveness, while parents had improved mindful parenting skills after the program. Other positive findings among the studies showed that mindfulness training had beneficial effects on adolescents with ASD (in terms of attention problems, externalizing and internalizing problems) and parents (in terms of parenting style, well-being, and parenting stress) (de Bruin et al 2015;Ridderinkhof et al 2017;Salem-Guirgis et al 2019). Apart from quantitative studies, a qualitative study was conducted to interview adolescents with ASD and their parents about the experience of participating in the MYmind program (Ridderinkhof et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Journal of Autism and Developmental Disorders on the child's behaviours in the past six months. The SRS has been used in the previous MYmind studies(de Bruin et al 2015;Ridderinkhof et al 2017;Salem-Guirgis et al 2019) and has been validated in Chinese version with an internal consistency of 0.87-0.92 and test-retest reliability of 0.81-0.94…”
mentioning
confidence: 99%